Pending question about the PIMS methodology: a brief account - Mosqueda Almanza, Rubén (Cuadernos de Administración, 2010)
We can assume that an appropriate strategy will have a positive impact on profits and it will contribute to having a company’s market share grow. Recent findings suggest that only the adaptation of a strategic plan can bring a company to perform at optimum levels. PIMS is an archetypical model to achieve that, but fundamental problems remain that limit it. This paper shows the evolution of the PIMS methodology and reveals its challenges and possible development. The adequate definition of this strategy, the redesign of the questionnaire PIMS, problems of Multicollinearity and the Market Share Effect would be the most relevant problems that this paper will address. The results show that there is a need to precisely define the strategy adopted by the company, to redesign the PIMS survey when applied to incomplete markets. And finally, it notes an advance in the PIMS econometric studies with emphasis on the variable Relative Quality of Product, in order to solve the thorny issue of market share effect on ROI.